The Efficacy of Therapeutic Plasma Exchange in Antiphospholipid Antibody-positive Patients With Spontaneous Intracerebral Hemorrhage and High D-dimer Levels. Issue 1 (January 2018) - Li, Chiao-Zhu; Liu, Feng-Cheng; Li, Chiao-Ching; Lin, Meng-Chi; Hsieh, Chih-Chuan; Lin, Bon-Jour; Chen, Nan-Fu; Chen, Chun-Lin; Chung, Tzu-Tsao; Tang, Chi-Tun; Hueng, Dueng-Yuan; Ju, Da-Tong; et al.
Abstract : Objective: We investigated the efficacy of plasma exchange (PE) in antiphospholipid antibody (aPL)-positive patients with a spontaneous intracerebral hemorrhage (ICH) and high D-dimer levels. Materials and Methods: From May 2013 to May 2016, we evaluated 32 patients who were below the age of 50 and presented with spontaneous ICH. Five patients were positive for aPL antibody and 3 had a higher level of D-dimer. These 3 patients underwent 5 sessions of PE using fresh frozen plasma as replacement fluid. We analyzed the days postadmission until PE-start, the days of intensive care unit (ICU) hospitalization, D-dimer series, Glasgow Coma Scale (GCS) scores, and modified Rankin scale (mRS) scores. D-dimer levels and GCS scores were recorded at both pre-PE and post-PE stages. The mRS scores were recorded at pre-PE stage and 3 months post-PE. Results: The mean postadmission period until PE-start was 8.33 days. The mean ICU hospitalization was 17.33 days. The D-dimer level pre-PE ranged from 2.34 to 5.44 mg/L fibrinogen equivalent unit (FEU). The D-dimer level post-PE ranged from 1.05 to 3.30 mg/L FEU. The amount of decline of the D-dimer level between pre-PE and post-PE ranged from 0.65 to 2.14 mg/L FEU. The GCS score pre-PE was between 7 and 8. The highest post-PE GCS score was 14. The improved GCS scores post-PE ranged from 3 to 6. The improved mRS scores of 3 months post-PE ranged from 3 to 4. Conclusions: The concurrent presence of positive aPL and a higher D-dimer level may worsen the neurological outcome of patients with a spontaneous ICH. Aggressive PE is effective for the treatment of such patients, decreasing the extent of the ICU hospitalization.